5.6(x-1)=-0.4x+36.4

Simple and best practice solution for 5.6(x-1)=-0.4x+36.4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5.6(x-1)=-0.4x+36.4 equation:


5.6(x-1)=-0.4x+36.4

We simplify the equation to the form, which is simple to understand
5.6(x-1)=-0.4x+36.4

Reorder the terms in parentheses
+(+5.6x-5.6)=-0.4x+36.4

Remove unnecessary parentheses
+5.6x-5.6=-0.4x+36.4

We move all terms containing x to the left and all other terms to the right.
+5.6x + 0.4x=+36.4+5.6

We simplify left and right side of the equation.
+6x=+42

We divide both sides of the equation by 6 to get x.
x=7

See similar equations:

| 2(y+6)=30 | | 13-p=-8 | | 13-p=8 | | 12x-2=58 | | (2x-3)/5+4=x-2 | | 13+(-12)-(-5)=? | | 4x-6=-122 | | 2(y+4)=26 | | 2(y+5)=26 | | 3-2=13 | | 7-5x=7+3x | | f-13+7=2 | | 3(y+7)=36 | | 12-1=4p+23 | | a^3+2a^2-25a-50= | | 2(y+6)=24 | | x+10=4x+1 | | -282-(+1,017)=? | | 2y+48=8 | | M^2-6=5m | | f(x)=25x+150 | | 141-6x=30x+21 | | 28+2x=6x | | 10x+4=29 | | -4.9t^2+19.6t+58.8=0 | | 6(y-5)=-6 | | 5(y+3)=55 | | b^2-4*b+4=0 | | 8x-32=18+6x | | 2x+8-4x-15=16+8x-2-3 | | (3x+6)= | | y=(3x/12)+105 |

Equations solver categories